Hiroaki Sato (trad.). A Brief History of Imbecility. Poetry and Prose of Takamura Kotaro. Honolulú: University of Hawaii Press, 1992, 261 pp. - Quartucci, Guillermo (Estudios de Asia y África, 1993)
-